Skill Formation, Temporary Disadvantage and Elite Education - Per Hjertstrand; Pehr-Johan Norbäck; Lars Persson (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Elite skills have become crucial in today's superstar economy. We develop a multi-period skill-formation model where we show that individuals with temporary disadvantages must exert greater effort to gain access to elite education. This "underdog-incentive effect" implies that "educated underdogs" obtain superior adult skills. We find support for this mechanism in soccer data: players born early in the year dominate youth soccer, but players born late (but not too late) in the year become the superstars. We also show that if young students discount the future "too much", high requirements to elite education can increase expected life-time welfare for disadvantaged students.
Keywords: I20; J24; D90; 330; skill formation; temporary disadvantage; elite education; soccer; underdog